Comparison of marital satisfaction by couples types in arranged (ta'aruf) married couples - Shahnaz Safitri; Yudiana Ratnasari (HUMANITAS: Indonesian Psychological Journal, 2019)
One form of marital arrangements in Indonesian Muslim society is to get married through arranged marriages, popularly called as ta'aruf. Ta'aruf is related to the individual's religiosity, which may be associated with high marital satisfaction. This study aimed to explore the comparison of marital satisfaction by couple types in the context of marriage through ta'aruf. This research involved 62 persons as couples (M of age = 25.35 years old) in Jakarta as participants. The Revised Dyadic Adjustment Scale (RDAS) and Relational Dimensions Instrument (RDI) were used to collect the data. The couple types were derived from K-Means cluster analysis on the RDI score which was further analyzed with one-way ANOVA to test for difference in marital satisfaction. The results show there is a significant difference in marital satisfaction among the couple types in the couples as general, and also particularly in men as husbands. However, marital satisfaction does not differ to the couple type among women as wives. Therefore, gender seems to influence this relationship since husbands and wives differ in their degree of marital satisfaction within the same couple types. The compatibility on the vision and marital scheme between the spouses may enforce to a high marital satisfaction.